Cultural universality and specificity of student engagement in school: The results of an international study from 12 countries - Lam, Shui-fong (2016)
The Hong Kong subproject was supported by the Quality Education Fund of the Education Bureau in Hong Kong, whereas the Portuguese subproject was supported by the Portuguese Foundation for Science and Technology and by the Institute of Education of the University of Lisbon. The data of this paper were part of the data collected in a multinational project initiated by the International School Psychology Association.